The effectiveness of problem-based serious games on learning and learning motivation in the context of 3D computer graphics / Meisam Moradi - Meisam , Moradi (2022)
This study was an attempt to realize the possible effects of a problem-based serious game, named 'Immersivio', on learning 3D computer graphics in order to mitigate the challenges undergraduate students have for learning 3D computer graphics in Malaysia. In addition, this study aimed at understanding the extent to which a problem-based SG can affect undergraduate students' learning motivation. Indeed, the literature shows that 3D computer graphic courses are replete with abstract notions and algorithmic concepts which make learning of it difficult. To this end, the researcher designed a quantitative study with a between subject design and aimed at implementing a treatment course using the problem-based SG. Prior to that, a problem-based SG was designed by considering principles of problem-based learning (i.e., higher order thinking, collaborative learning, and cognitive thinking) and serious games (playing for learning). The problem-based model presented by Hmelo-Silver (2004) was used as the basis of the game design. A non-random sampling procedure (purposive sampling) was used in this quasi-experimental study and the participants formed 2 groups, i.e., the experimental group (n= 24) and the control group (n= 26). The independent samples t-test results indicated that the experimental group's posttest scores in a 3D computer graphics course were significantly affected as a result of using Immersivio. In addition, MANOVA test results indicated that the experimental group participants who had experienced Immersivio were more motivated to learn 3D computer graphics in terms of extrinsic motivation, intrinsic motivation, interest, attainment, cost, identification with academics, self-efficacy, and instrumentality. As the problem-based SG designed used in this study proved to be effective, its main constituents were extracted to design a framework of PBL-SG in learning 3D computer graphics. The main constituents considered were time, distance, number of used tools, and number of attempts. This study and the game design in this study can have pedagogical and practical implications for 3D computer graphics lecturers and those who are interested in designing effective problem-based SGs.